(untitled) (American Journal of Management, 2021)
The paper introduces categorical stereotypes to the literature on organizations categories. Stereotypes are information that can be transferred from group level to individual members of the group; to understand how firms respond to been categorized, scholars must account for the stereotypes associated with the categories. Stereotypes also influence audiences’ actions towards categorized firms; audiences go beyond judging organizations based on their categorical purity and consider information signals coming from stereotypes on the underlying categories. We explore the implications of categorical stereotypes on ongoing discourse on firm categories and on managerial actions.